2015
DOI: 10.1002/joc.4478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of statistical bias correction on the projected climate change signals of the regional climate model REMO over the Senegal River Basin

Abstract: We assess the impact of a statistical bias correction method based on histogram equalization functions on the projected climate change signals of regional climate model (RCM) simulations over the Senegal River Basin in West Africa. Focus is given to projected changes in precipitation, temperature, and potential water balance (P-PET) following the RCP4.5 and RCP8.5 emission scenario pathways by the end of the 21st century (2071-2100) compared to the 1971-2000 reference period. We found that applying the bias co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
(51 reference statements)
1
27
0
1
Order By: Relevance
“…Mbaye et al () working in western Sahel over the Senegal River Basin showed that precipitation would decrease by the end of the century for most parts of the study area with the exception of the southern part (Guinean Highlands). Potential water yield (the difference between precipitation and potential evapotranspiration) would decrease as well.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Mbaye et al () working in western Sahel over the Senegal River Basin showed that precipitation would decrease by the end of the century for most parts of the study area with the exception of the southern part (Guinean Highlands). Potential water yield (the difference between precipitation and potential evapotranspiration) would decrease as well.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, more research is needed to better understand, with less uncertainty, the direction and magnitude of climate change impacts over West Africa. In that sense, multimodel assessment approach is thus expected to capture the uncertainties in the modelling of climate change impacts (Mbaye et al, ; Oyerinde et al, ; Yira et al, ). The objectives of this study are therefore, for the Beninese part of the Niger River Basin, to statistically downscale the outputs of RCMs and assess future climate trends; quantify the impact of climate change on future blue water (BW) and green water (GW) availability; and quantify the uncertainty associated with the evaluation of BW and GW. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bodian et al [16] used a model at monthly step to predict streamflow which is not adapted for flood and base-flow modeling. Recently, Mbaye et al [17] used the regional climate model REMO as input for the Max Planck Institute for Meteorology-Hydrology Model (MPI-HM) and found general decrease of river discharge, runoff, evapotranspiration, soil moisture under the two Representative Concentration Pathways (RCP4.5 and RCP8.5) by the end of the century in the Upper Senegal Basin (West Africa) at Bakel station. Mbaye et al [17] did not take into account the effect of Manantali dam in the river and used only one climate model which can bias the results.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mbaye et al [17] used the regional climate model REMO as input for the Max Planck Institute for Meteorology-Hydrology Model (MPI-HM) and found general decrease of river discharge, runoff, evapotranspiration, soil moisture under the two Representative Concentration Pathways (RCP4.5 and RCP8.5) by the end of the century in the Upper Senegal Basin (West Africa) at Bakel station. Mbaye et al [17] did not take into account the effect of Manantali dam in the river and used only one climate model which can bias the results. In the Gambia River Basin, only the study of Ardoin-Bardin et al [18] was interested to the impact of climate on river basin water resources at Gouloumbou station by using four GCM (CSIRO-Mk2, ECHAM4, HadCM3 and NCAR-PC) under the AR3 (A2) scenario and the GR2M hydrological model.…”
Section: Introductionmentioning
confidence: 99%